PENYULUHAN HIDROPONIK METODE NUTRIENT FILM TECHNIQUE (NFT) UNTUK SAYURAN DAUN DI PT GREAT GIANT PINEAPPLE - Ali, Fahri (Politeknik Negeri Lampung, 2023)
The service activity with the title Hydroponic Counseling Nutrient Film Technique (NFT) Method for Leaf Vegetables at PT Great Giant Pineapple was attended by 11 employees. PT GGP, especially the LOB plant section, will develop a business of cultivating horticultural crops other than fruits. The company has available facilities and infrastructure needed for hydroponic cultivation. However, there is still a lack of knowledge for the implementation of the NFT hydroponic system, so training in the NFT hydroponic system is needed for the experts who work there. Polinela as a partner of PT GGP, especially lecturers of the Horticultural Crop Production Technology study program, facilitates NFT system hydroponic training which is also very capable in the field of hydroponics to assist partners (PT GGP) in using and utilizing the hydroponic installations they already have. This training was carried out by delivering material on hydroponic cultivation, NFT systems, calculation and dissolution of nutrients; discussions, and direct demonstrations. Demonstration activities on nursery activities on rockwoll media and direct checks on installations that have been installed by discussing problems in the field. The results of the discussion included: The roof of the green house is too short; The table frame in each gully is too far away; There is no bypass between the pipe connection from the nutrient tank to the gully connecting pipe; The pipe between the outline hose to return to the nutrient tank is as flat as the floor; The distance between the netpot in each planting hole is too close to the bottom of the gully, The nutrient tank is a white storage box which can cause the nutrients in it to heat up faster. During the activity, participants were actively involved in asking questions and sharing experiences and obstacles faced during hydroponic cultivation. During the activity, participants found solutions to their problems. The service team opens space and time for participants to communicate via whatsapp if they find problems. The results of this service activity are pakchoy seeds that have been sown and 7-day-old pakchoy seeds that the service team brought. The results of the activities that have been carried out can be concluded that the implementation of this service activity can increase the knowledge and skills of PT. GGP employees in cultivating leaf vegetable plants in the hydroponic NFT system.